Review of research on language anxiety related to language skills and three stages of language learning - ŁUSZCZYŃSKA, SYLWIA (Glottodidactica, 2017)
This article presents the findings of selected empirical research on language anxiety, conducted in various countries and among age groups at diverse proficiency levels, applying different research designs and anxiety measurement instruments. First of all, the role of some language skills in anxiety production is presented. The studies summarized below focus on listening, reading and writing in order to more specifically classify the causes of language anxiety. Then, a discussion of the relationship between anxiety during the three stages of language processing (i.e. input, processing, output) and its relationship to learning deficits is presented.